Front Cover. Issue 4 (27th December 2022) - Unknown
Abstract : The hospital environment has unique microbiological characteristics that require extensive management to avoid contamination of both humans and the natural environment. Label‐free Raman spectroscopy is an effective tool for this purpose with various applications ranging from infectious disease diagnostics over infection control to food and water safety. The review by A. Pistiki et al. present and discuss Raman‐based analytical methods and their applicability in the different areas of the hospital environment. Further details can be found in the article by Aikaterini Pistiki, Markus Salbreiter, Salwa Sultan, Petra Rösch, and Jürgen Popp (e202200011) Abstract : The hospital environment has unique microbiological characteristics that require extensive management to avoid contamination of both humans and the natural environment. Label‐free Raman spectroscopy is an effective tool for this purpose with various applications ranging from infectious disease diagnostics over infection control to food and water safety. The review by A. Pistiki et al. present and discuss Raman‐based analytical methods and their applicability in the different areas of the hospital environment. Further details can be found in the article by Aikaterini Pistiki, Markus Salbreiter, Salwa Sultan, Petra Rösch, and Jürgen Popp (e202200011)